(untitled) (International Journal of Mathematics and Physics, 2012)
The morphology and properties of metallized hydrophilic polymer are investigated on an atomic force microscope Ntegra Therma (the company "NT-MDT", Zelenograd, Russia). The atomic force microscopy is one of the foremost tools for imaging, measuring, and manipulating matter at the nanoscale. The information is gathered by "feeling" the surface with a mechanical probe. A special technique of atomic force microscopy was picked for qualitative analysis of samples based on polymeric materials. It was shown that the introduction of small amounts of PANI (0.01-0.02 wt.%) results in the data of atomic force microscopy which show that in the presence of an electrically conductive polymer structure the system changes significantly. Comparing the metallized with silver different polymer systems, the quality of the surface metallization of PI + PANI is higher than the surface of the polymer system PI-PU: the silver particles are uniformly distributed on the surface of the PI + PANI and the average particle size of silver from 75 to 150 nm.